2007
DOI: 10.1017/s1431927607070419
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy of Removal of Dentin Smear Layers

Abstract: The regular periodontal practice of scaling and root planing produces a smear layer on the root surface that is detrimental to the readhesion of tissues during subsequent regeneration therapy. Although it has been demonstrated that gels containing the chelating agent ethylenediaminetetraacetic acid (EDTA) can assist in the removal of this contaminating layer, no quantitative method is yet available by which to evaluate the efficiency of the treatment. In this article, the power of atomic force microscopy (AFM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Despite the tendency for a decrease in the BS of Vitrebond to the smear-free dentin, no statistically significant difference was found among the four groups. Batista et al (22) demonstrated that the dentin treated with EDTA is much rougher than the smear-covered dentin. This fact could add to the interlocking of Vitrebond to smear-free dentin and might explain the statistically similar BS values obtained in the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the tendency for a decrease in the BS of Vitrebond to the smear-free dentin, no statistically significant difference was found among the four groups. Batista et al (22) demonstrated that the dentin treated with EDTA is much rougher than the smear-covered dentin. This fact could add to the interlocking of Vitrebond to smear-free dentin and might explain the statistically similar BS values obtained in the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Then, patients were assigned to one of two treatment groups by the selection of sealed envelopes containing a paper labeled “group 1” or “group 2.” In the event the patient had multiple defects, all defects were assigned the same treatment. The root surfaces were burnished with a cotton pellet soaked with 24% ethylene diamine tetraacetic acid gel ‖ for 2 minutes in an effort to remove the smear layer, 20 detoxify the root surface, expose collagen fibrils, 21 and, in the case of group 2, facilitate the precipitation of enamel matrix proteins onto the root surface 22,23 . Then the area was irrigated with 0.9% sterile saline.…”
Section: Methodsmentioning
confidence: 99%
“…The AFM provides 3D highresolution images because it has a software with great mathematical accuracy for the mapping and characterization of surfaces~Silva Batista et al, 2007;Kakaboura et al, 2007! providing quantitative data on the length of marginal gaps.…”
Section: Resultsmentioning
confidence: 99%